Perancangan Alat Sensor Pendeteksi Kebocoran Gas LPG dan Api dengan Menggunakan MQ-2 Dan Flame Sensor - Ferda Denaya Argarizal Purnama; R. Tommy Gumelar; Shevti Arbekti Arman (ITB Ahmad Dahlan Jakarta, 2023)
LPG gas leaks can become a serious threat to human safety and health, especially if they are not detected quickly and accurately in the main control system for this LPG gas leak detection system and even if the worst possibilities occur, such as a spark which could result in a light fire. This research uses the Prototype method. Another goal is to minimize the risk of accidents when using LPG gas stoves, and reduce the risk of damage and material losses arising from gas leaks and fires caused by LPG gas stoves. Design and manufacture of hardware and software by developing the MQ-2 sensor detection algorithm which is used to detect gas leaks and Flame sensors for fire detection. Testing is carried out by simulating various test scenarios from the use of gas sensors and fire sensors. The test results show that this system is capable of detecting detected gas and fire. Tests are carried out alternately between gas sensors and fire sensors. The output on the system is in the form of SMS notifications, Bazzer and LED lights. SMS notification using SIM800L. When a fire is detected there will be an SMS notification